Eight Years of Multiparty Democracy in Mozambique: The Public’s View - João Pereira; Ines Raimundo; Annie Chikwanha; Alda Saute; Robert Mattes (Afrobarometer Working Papers, 2003)
Since its emergence from a brutal, 17-year civil war, Mozambique’s process of political reform has faced a number of challenges. The first has been to empower ordinary Mozambicans by allowing them to participate in a democratic system and enabling them to voice their demands to the state and hold it accountable. The second has been to rebuild a state with the capacity to respond to citizen demands effectively. And given the long history of violent division, a third challenge has been to build a state that enjoys broad legitimacy – a legitimacy that spans the bitter partisan divides of the past, enabling the formation of a strong, authoritative state with the ability to enforce the rule of law, but also the discipline to rule through transparent procedures. Perhaps the best evidence by which to judge the success of the process of political reform are the opinions of ordinary Mozambicans. Rather than looking to expert judgments or to measures of formal constitutional rights, we believe that the views of ordinary citizens – as the ultimate consumers of what democratic governments supply – can offer perhaps the most conclusive assessment of the quality of governance. What do they say? Through its partner in Mozambique, the Public Opinion Service of the Centre for Population Studies at the University of Eduardo Mondlane, the Afrobarometer surveyed a nationally representative sample of 1425 Mozambicans citizens, aged 18 years and older, using a multi-stage, area-stratified, clustered sample designed by the National Institute for Statistics. The survey was carried out between August and October 2002 in all 10 provinces of the Republic of Mozambique. At a confidence level of 95 percent, a sample of this size allows a confidence interval, or margin of error, of plus or minus 2.5 percent. This means that, had we interviewed every Mozambican, 19 times out of 20 the results would differ from those of this survey by no more than 2.5 percent. The evidence from this survey suggests that although Mozambique is plagued by what appear to be insurmountable problems, in general the country appears to be on the right path as an emerging democracy. While the society faces vast challenges of building human and social capital to empower citizens further and increase the capacity of the state, the democratization that has occurred since Mozambique opened its political space has gone a long way in propelling democracy forward.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; accountability / responsabilização; civil society / sociedade civil

Endangering safe motherhood in Mozambique: prenatal care as pregnancy risk - Chapman, Rachel R. (Social Science & Medicine, 2003)
Despite high infant and maternal mortality rates, many Mozambican women with access to prenatal services delay prenatal clinic consultations, limiting opportunity for prevention and treatment of preventable pregnancy complications. Ethnographic research, interviews with health providers and longitudinal pregnancy case studies with 83 women were conducted in Central Mozambique to examine pregnant women's underutilization of clinic-based prenatal services. The study found that pregnancy beliefs and prenatal practices reflect women's attempts to influence reproduction under conditions of vulnerability at multiple levels. Women reported high maternal reproductive morbidity, frequent pregnancy wastage, and immense pressure to bear children throughout their reproductive years. Reproductive vulnerability is intensified by poverty and an intense burden placed on poor, peri-urban women farmers for family subsistence and continuous fertility in a period of economic austerity, land shortages, and increasing social conflict and inequality. In this environment of economic insecurity exacerbated by congested living conditions, women report competing for scarce resources, including male support and income. This vulnerability heightens women's perceptions that they and their unborn infants will be targets of witchcraft or sorcery by jealous neighbors and kin. They respond by hiding pregnancy and delaying prenatal care. Within the context of women's perceived reproductive risks, delayed prenatal care can be seen as a strategy to protect pregnancy from purposeful human and spirit harm. Women mobilized limited resources to acquire prenatal care outside the formal clinic setting. It is concluded that provision of clinical prenatal services is insufficient to reduce reproductive risks for the most socially and economically marginal since it is their vulnerability that prevents women from using available services. Confidential maternity services and social safety nets for greater economic security are recommended.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

New Rules, New Roles: Does PSP Benefit the Poor? Small-Scale Private Sector Participation in Niassa, Mozambique - Jose Atanasio David; Lindsey Breslin (Estamos organização comunitária, 2003)
This case study has attempted to show that the implementation of a policy mechanism like PSP in water and sanitation in a context like Niassa is highly unlikely to achieve the development impacts intended. It appears that the concept “PSP” itself is erroneous; it assumes that there is a private sector wishing to participate, and that public sector delivery is the key obstacle to private involvement. Equally erroneous is the idea that the private sector can just emerge from market mechanisms that are assumed to be existent. The market itself, and he relationships that typically exist within it, need to be constructed first. Niassa is an example of an extremely impoverished area where the cashpoor local economy and damaged social institutions currently could not support and sustain the emergence of a viable private sector.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; health - WASH / saúde - água, higiene e saneamento; health / saúde; private sector / setor privado